In vitro expansion of GGC:GCC repeats: identification of the preferred strand of expansion. - Ji, J (1996)
The human fragile-X syndrome, a major cause of inherited mental retardation, is associated with expansion of the trinucleotide repeat GGC:GCC. Repetitive sequences in DNA are subject to slippage during catalysis by DNA polymerases. We characterized the extent of slippage of synthetic GGC:GCC repeats by various DNA polymerases: Taq DNA polymerase, Klenow fragment of DNA polymerase I, DNA Sequence, DNA polymerase-alpha and polymerase-beta, as well as HIV reverse transcriptase. All of these enzymes were found to expand GGC:GCC repeats, with the most extensive expansion exhibited by Taq DNA polymerase. Starting with a template and primer, each 15 nucleotides (nt) in length, the product of one round of synthesis by Taq polymerase is as long as 250 nt. Sequence analysis of cloned DNA fragments expanded by Taq polymerase indicates that expansion involves multiple triplet additions and that it is asymmetric. The asymmetric distribution of terminal nucleotides in the expanded product is consistent with active expansion of the GCC strand and passive additions onto the GGC strand. The preferential elongation and expansion of the GCC strand was confirmed in studies utilizing longer repeats within a single-stranded M-13 template.